Analysis of Visual Elements of Cubism in Western Modernist Art - Liu, Jilin; Liu, Zhao; Zhang, Yuhang (Transactions on Social Science, Education and Humanities Research, 2024)
This paper takes Cubism in Western modernist art as the research object, focusing on the analysis of its visual elements deconstruction and reconstruction of expression techniques. The research background is based on Cubism as an important school of modern art, its challenge and breakthrough to the traditional art concept laid the foundation for the development of modern art. At present, there is still a large space for discussion on the analysis of cubism visual elements and its enlightenment in the field of modern design. Through the analysis of the processing techniques and visual elements in Cubism works, we can see that the visual expressiveness in Cubism still has an important role in the contemporary art design creation.